Serum levels of secretory IgA and in vitro production of IgA in rheumatoid arthritis (1993)
Twenty-three per cent of rheumatoid arthritis (RA) patients show an increase of serum IgA concentrations. To determine the role of mucous-associated lymphoid tissue (MALT) in the elevation of serum IgA in RA, we studied the serum secretory-IgA (s-IgA) in 63 RA patients and in 30 healthy controls. We also analysed the secretion of circulating B cells producing IgA, which is known to reflect mucous tissue activity, in a subgroup of 15 patients with increased serum IgA concentrations, and in control patients. The mean s-IgA in the RA patients was 0.046 mg/ml +/- 0.064, versus 0.002 +/- 0.004 mg/ml in controls (not significant). Active disease defined by clinical criteria was associated with an increase in serum s-IgA (p < 0.001). Furthermore, in a subgroup of RA patients with high serum IgA levels, we found an increase in in vitro IgA production by circulating blood lymphocytes (17.39 +/- 15.2 micrograms/ml), versus RA patients with normal serum IgA levels or controls (p < 0.001). These results were not modified by LPS or PWM. Our results further support the hypothesis of primary MALT activation following environmental antigenic stimulation in RA patients.